An integrated approach and IT platform to optimise electric motor engineering and design. (1st January 2014) - Favi, Claudio; Germani, Michele; Marconi, Marco; Mengoni, Maura
Electric motors are one of the most common electrical components. The design phase is the most important stage in which 'green' customised solutions can be ideated, evaluated and optimised. Different aspects have to be concurrently addressed to achieve a high quality product in a short time to market. The present paper describes an innovative approach and software platform to configure and simulate customised electric motors. A key feature of the platform is a knowledge-based system that aims to standardise the design process. The platform integrates different software tools to support the development and verification of several design aspects, such as energy efficiency, manufacturing costs and environmental impacts. It also provides a collaborative area to support collaboration along the whole supply chain. Different case studies are presented to show the effectiveness of the platform application in supporting designers in the creation of innovative products.